Maturational delay in ADHD: evidence from CPT - Berger, Itai; Slobodin, Ortal; Aboud, Merav; Melamed, Julia; Cassuto, Hanoch (Frontiers in Human Neuroscience, 2013)
While data from behavioural, neuropsychological, and brain studies suggested that Attention-Deficit/Hyperactivity Disorder (ADHD) is related to a developmental lag that reduces with age, other studies have proposed that ADHD represents a deviant brain function. The present study used a cross-sectional approach to examine whether ADHD children show a developmental delay in cognitive performance measured by continuous performance test (CPT). We thus compared six age groups of ADHD children (N=559) and their unaffected peers (N=365), aged 6-11, in four parameters of MOXO-CPT performance: Attention, Timing, Hyperactivity and Impulsivity. Results have shown that despite improvement in CPT performance with age, ADHD children continued to demonstrate impaired performance as compared to controls. In most parameters, CPT performance of ADHD children matched that of 1-3 years younger normal controls, with a delay most prominent in older children. However, in the Hyperactivity parameter, ADHD children’s performance resembled that of much younger healthy children, with almost no evidence for a developmental catch up. This study suggests that while some cognitive functions develop slower but normally, other functions (e.g., inhibitory control) show a different sequel.